2016
DOI: 10.7314/apjcp.2016.17.4.2285
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Positive Diffuse Large B-Cell Lymphoma: is it different between Over and Under 50 Years of Age?

Abstract: Background: Epstein-Barr virus (EBV) positive diffuse large B-cell lymphoma (DLBCL) of the elderly is an entity introduced in the latest WHO classification of lymphoid tumors and defined in patients older than 50 years without prior lymphoma or immunodeficiency. However, recently it has also been seen in patients under 50. There is thus debate as to whether these are separate entities. Materials and Methods: In this retrospective study, we analyzed de novo DLBCL admitted to our institute over a period of two y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…We also observed that EBV‐neg patients with poor PFS also presented the highest proportions of TIM‐3 + CD4 + T cells. Similar to previous reports in NHL of immunocompetent patients, 42 which generally are EBV‐negative 43 . In our study, NK cells from EBV‐neg PTLDs also overexpressed TIM‐3, an immune‐checkpoint normally expressed by mature 44 and exhausted 45‐49 NK cells, the anti‐tumoral functions of which can be reversed after TIM‐3 antagonization 49 .…”
Section: Discussionsupporting
confidence: 90%
“…We also observed that EBV‐neg patients with poor PFS also presented the highest proportions of TIM‐3 + CD4 + T cells. Similar to previous reports in NHL of immunocompetent patients, 42 which generally are EBV‐negative 43 . In our study, NK cells from EBV‐neg PTLDs also overexpressed TIM‐3, an immune‐checkpoint normally expressed by mature 44 and exhausted 45‐49 NK cells, the anti‐tumoral functions of which can be reversed after TIM‐3 antagonization 49 .…”
Section: Discussionsupporting
confidence: 90%
“…EBV accounts for 0.5-2% cancers in different geographical regions of the world, The recent analysis indicates that 1.8% of all cancer deaths in 2010 were associated with EBV. EBV is closely associated with human malignancies, including Burkitt's lymphoma (BL), Hodgkin's disease (HD), T-cell lymphoma, nasopharyngeal carcinoma (NPC), a subset of gastric carcinoma and lung carcinoma with lymphoepithelioma-like histology (Ishtiaq et al, 2013., Leila et al, 2016Monabati et al,2016;Khan et al, 2014;Jha et al, 2016). Several mechanisms and hypotheses have been described regarding the association between EBV infection and breast carcinoma (Zekri et al, 2012;Reza et al, 2015;Tempera et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…EBV-positive DLBCL of the elderly was introduced in the 2008 World Health Organization classification of lymphoid neoplasms as a provisional entity restricted to patients older than 50 years and is in general associated with a poor prognosis. 23 However, a recent study comparing older and younger patients reported no significant clinical differences, 24 leading to the extension of this subtype to all ages in the 2016 revision of the classification. Its prevalence is estimated between 5% and 15% of all DLBCL cases, 23 but because EBV testing is not systematically performed at diagnosis, many cases are probably managed as EBV-negative DLBCLs.…”
Section: Discussionmentioning
confidence: 99%